STUDI TENTANG WAKTU KONSEPTUAL DAN WAKTU PERSEPTUAL SERTA PENGGUNAANNYA - Muara Lumbatoruan, - (1985)
The study on conceptual and perceptual time and its usage is concerned with human conception of time, the perception of time, the aims and activity levels in time usage, and time structuring according to transactional analysis. The reasons for choosing the problem are: That the problem is perennial. Time and its usage is an important factor in daily life; found in school curriculum. This is a very difficult problem and full of mystery. The research objectives are to collect verious ap -proches on the concept of time and to use time for living a good life. To identify the perception and dimension of time. To explain the structure of time usage according to transactional analysis and to know the substantial objectives for counseling; i.e. helping curriculum completion, to help students in structuring their time and to develop leisure time guidance as a new area in learning guidance activities. The problems approaches are through qualitative survey and reflective thinking, to explore various theo -ries of space and time of some scientists an philosophers from reading material. The research, findings are : 1) Conceptual time is differentiated from perceptual time. Conceptual space and time are the idealized idealized space and time of which we think when we ask about their nature and its implications, or to which the philosophers refer when they ask whether they are limited or unlimited, sutgedtive or objective. Perceptual time is the time which we experience day by day ; and perceptual space is the space in which we live and move. 2) The traditional vew is that space and time existing in reality, as seperate entities. The other view stated that space and time are something that is continuously changing, moves in a direction not contained in itself. Time is existing within the consciousness through sense experiences, and as a single eternal moment. Time is a real duration that signifies both undivided contiuity and creation (known by intuition), something relative ; as a fourth dimention and space and may be considered as spiritual entity that incubates in the third dimen -sion for creating everything beautiful and wonderful. 3) Perceptual time has educational, productive, substitutional, containing bonus, total cost and socio-psy -chological values. It has specific, accurate, and limited measurement. Time perspective includes mental